2013
DOI: 10.1007/s10856-013-5063-6
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of osteoblast-like cells on calcium-deficient hydroxyapatite ceramics composed of particles with different shapes and sizes

Abstract: In designing the biomaterials, it is important to control their surface morphologies, because they affect the interactions between the materials and cells. We previously reported that porous calcium-deficient hydroxyapatite (HA) ceramics composed of rod-like particles had advantages over sintered porous HA ceramics; however, the effects of the surface morphology of calcium-deficient HA ceramics on cell behavior have remained unclear. Using a hydrothermal process, we successfully prepared porous calcium-deficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Consequently, high surface roughness restricts cell adhesion and proliferation. Earlier studies also have reported that cell proliferation was suppressed on plate-like morphologies with sharp tips (widths < 1 μm) compared to smoother surfaces without sharp features which attributed to larger contact domains on smoother surfaces [47].…”
Section: Effect Of Surface Morphology On Cell Proliferation Viability and Gene Expressionmentioning
confidence: 82%
“…Consequently, high surface roughness restricts cell adhesion and proliferation. Earlier studies also have reported that cell proliferation was suppressed on plate-like morphologies with sharp tips (widths < 1 μm) compared to smoother surfaces without sharp features which attributed to larger contact domains on smoother surfaces [47].…”
Section: Effect Of Surface Morphology On Cell Proliferation Viability and Gene Expressionmentioning
confidence: 82%
“…This behavior may be attributed to the larger contact surface area between the cells and the coating [ 20 , 65 ]. Kamitakahara et al [ 66 ] reported that the wide contact surface area is an important factor for cell proliferation and cells could proliferate easily. Mokabber et al [ 20 ] indicated the smooth surface of calcium phosphate coatings resulted in better proliferation of the cells, whereas the rough calcium phosphate coatings restricted cell adhesion and consequently cell proliferation.…”
Section: Resultsmentioning
confidence: 99%
“…Hydroxyapatite (HA) is a major chemical constituent of skeletal bone, and it is converted into Ca 2+ and PO 4 3- in the body ( Couto et al, 2010 ). When utilized in orthopedics, HA promotes bone development and osteointegration, possibly by increasing adhesion and osteoblast proliferation, resulting in faster healing of bone ( Kamitakahara et al, 2014 ). Therefore, HA promotes osteoblast bioactivity to speed-up bone regeneration ( Lin et al, 2009 ; Iafisco et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%